CSI-based human activity recognition via lightweight compact convolutional transformers - Wong, Yan Chiew; Abuhoureyah, Fahd Saad Amed; Al-Taweel, Malik Hasan; Abdullah, Nihad Ibrahim (Techno-Press, 2024)
WiFi sensing integration enables non-intrusive and is utilized in applications like Human Activity Recognition (HAR) to leverage Multiple Input Multiple Output (MIMO) systems and Channel State Information (CSI) data for accurate signal monitoring in different fields, such as smart environments. The complexity of extracting relevant features from CSI data poses computational bottlenecks, hindering real-time recognition and limiting deployment on resource-constrained devices. The existing methods sacrifice accuracy for computational efficiency or vice versa, compromising the reliability of activity recognition within pervasive environments. The lightweight Compact Convolutional Transformer (CCT) algorithm proposed in this work offers a solution by streamlining the process of leveraging CSI data for activity recognition in such complex data. By leveraging the strengths of both CNNs and transformer models, the CCT algorithm achieves state-of-the-art accuracy on various benchmarks, emphasizing its excellence over traditional algorithms. The model matches convolutional networks’ computational efficiency with transformers’ modeling capabilities. The evaluation process of the proposed model utilizes self-collected dataset for CSI WiFi signals with few daily activities. The results demonstrate the improvement achieved by using CCT in real-time activity recognition, as well as the ability to operate on devices and networks with limited computational resources.